Hidden Brazilian Amazon diversity: four new species, redescription and notes on natural history of Termitozophilus Silvestri, 1901 (Coleoptera: Staphylinidae: Aleocharinae) - Da Silva, Ruan Felipe; Zilberman, Bruno; Carvalho-Filho, Fernando Da Silva (Zootaxa, 2022)
The genus Termitozophilus Silvestri (Coleoptera: Staphylinidae: Aleocharinae: Corotocini) is composed of three species that are associated with termite nests of the genus Cornitermes Wasmann in South America. Although this termite genus is widespread in the Amazon region, the species of the rove beetle genus Termitozophilus associated with it are less known. In this paper, we describe four new species of Termitozophilus species from the Brazilian Oriental Amazon. Furthermore, we provide information on natural history, post-imaginal growth, behavior, and a taxonomic key to all valid species.